Factors affecting the success of women’s entrepreneurship: a review of literature - Cabrera Gil Grados, Ezilda María (2017)
Women entrepreneurship has grown significantly all over the world, and it is widely established that entrepreneurship is important for economic growth and wealth. Despite those facts, women’s participation in entrepreneurship is lower than men’s in almost all societies. Those phenomena get the attention of scholars from diverse disciplines, all of them interested in the behaviour and profile of female entrepreneurs and their business success rates. Several isolated factors were studied, with positive and negative effects on each stage of the entrepreneur process, for women entrepreneurs, so the purpose of this research is identify, classify by their impact and organise those factors in relation to the stages of the entrepreneur process.